Learning management system utilization among Malaysian higher education students: a confirmatory factor analysis - Zadeh, Sousan Baleghi; Mohd Ayub, Ahmad Fauzi; Mahmud, Rosnaini; Mohd Daud, Shaffe (American Research Institute for Policy Development, 2014)
Today, the number of universities equipped with leaning management system (LMS) is increasing. However, the true potential of LMS is not yet fully utilized to support learning activities. Studies in the domain of LMS utilization will help universities to enhance their knowledge of educational management. A validated instrument in the domain of LMS utilization will assist lecturers to integrate it in the process of teaching and learning and increase the quality of learning. There are different factors which may affect LMS utilization among students and lecturers, but in the present study only four factors were investigated. Among the four factors, three were adopted from Technology Acceptance Model (perceived ease of use, perceived usefulness, behavior intention to use) and one was adopted from Theory of Reasoned Action (subjective norm).The purpose of the present study is to provide a confirmatory test for the proposed measurement model. The participants were 216 students at University Putra Malaysia (UPM) and the instrument used was a questionnaire with 39 items. After testing the proposed measurement model, ten items were deleted because of crossloading. The result of testing the proposed modified measurement model revealed that the theoretical measurement model was fit and validated with the data of the present study.